Characterization of potential anti-diabetic related-proteins from Pleurotus Pulmonarius (Fr.) Quel. (grey oyster mushroom) / Nurul Azwa Abd Wahab - Nurul Azwa , Abd Wahab (2014)
Diabetes mellitus is a chronic metabolic disorder due to carbohydrate, fat and protein metabolism disturbances, resulting from defects of insulin secretion (Type 1), increased cellular resistance to insulin (Type 2) or both. Diabetes is characterized by an abnormally high level of blood glucose (hyperglycemia) that leads to serious damage of the body organs. World Health Organization estimates almost 220 million people worldwide diagnosed by diabetes and likely to be doubled by the year 2030. Furthermore, untreated diabetes will contribute to complications such as heart disease, stroke, hypertension, nervous system disease and amputation. Currently, researchers approach for an alternative therapeutic for combating the most prevalent diabetes, which is type 2 diabetes, by delaying the absorption of carbohydrates/glucose through inhibition of carbohydrate hydrolysing enzymes; α-amylase and α-glucosidase enzymes. Previous research reported that Pleurotus pulmonarius (Fr.) Quél. has a good potential in reduction of hyperglycemia in type 2 diabetes and ameliorates the course of cardiovascular-related complications. Bioactive compounds from P. pulmonarius sources are considered to be less toxic and free from side effects compared to synthetic drugs available in market such as sulfonylureas, biguanides, glinides, tolbutamide, troglitazone, rosigitazone and repaglinide. Besides, the production of P. pulmonarius has been increasing worldwide at a rapid rate due to its broad adaptability, aggressiveness, ease of cultivation with high yield potential and high nutritional value. According to Icons of Medicinal Fungi from China, the medicinal part of the oyster mushroom is in its basidiocarps. Hence, the present study aims to isolate and to characterize potentially active protein from P. pulmonarius basidiocarps. Crude aqueous, methanol, dichloromethane and polysaccharide extracts as well as ammonium sulphate precipitated protein fraction (F10-F100) from P. pulmonarius basidiocarps were explored. All samples were tested via Saccharomyces cerevisiae α-glucosidase and porcine α-amylase inhibitory assays in vitro. Preliminary results demonstrated that at 25 μg/ml, F30 protein fraction inhibited α-glucosidase with 24.18% and F100 protein fraction inihibited α-amylase activity with 41.80%. Nevertheless, crude aqueous, methanol, dichloromethane, polysaccharide extracts at 25 mg/ml showed meagre inhibitory activities towards both assays. Selected anti-diabetic inhibitors F30 and F100 protein fractions showed a very distinct SDS-PAGE protein bands profile, 10 (5-70 kDa) and 9 protein bands (6-70 kDa) respectively thereby, both samples were further purified by RP-HPLC. Following RP-HPLC, peak 3 at 2.5 μg/ml demonstrated 25% inhibition towards α-glucosidase (F30) but very low inhibition for α-amylase activities at 6.25 μg/ml with only 2.84% (F100). Characterization of peak 3 protein from F30 protein fraction using MALDI-TOF/TOF mass spectrometry identified four different proteins, which could be involved in the regulation of blood glucose level via various mechanisms. This study revealed the presence of several anti-diabetic related proteins such as profilin-like protein (in-solution MALDI-TOF/TOF MS), glyceraldehyde-3-phosphate dehydrogenase-like protein, trehalose phosphorylase-like protein and catalase-like protein (in-gel MALDI-TOF/TOF MS), thus suggests that the basidiocarps of P. pulmonarius has high potential in lowering blood glucose level, reduce insulin resistance and the risk of diabetic-related complications.